2009
DOI: 10.1111/j.1440-0960.2009.00537.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent keratoacanthoma with vascular invasion: A diagnostic and management dilemma

Abstract: A 71-year-old man with chronic renal failure and on peritoneal dialysis presented with recurrence of multiple keratotic nodules along a surgical scar. This was 6 months after the excision of a recurrent keratotic nodule reported as squamous cell carcinoma from the same site. The lesions were initially reported as squamous cell carcinomas, but on review of histology were consistent with keratoacanthomas. One of the keratoacanthomas showed vascular invasion. These responded well to low-dose acitretin at 10 mg th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Neural invasion of KA, as well as a few cases of vascular invasion, have been described in a number of papers. [18][19][20][21][22][23] The biological behaviour in all studies and all reported cases have, without exception, been benign, with only few local recurrences treated successfully with operation. This is in contrast to the behaviour of perineural invasion of cutaneous SCCs.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Neural invasion of KA, as well as a few cases of vascular invasion, have been described in a number of papers. [18][19][20][21][22][23] The biological behaviour in all studies and all reported cases have, without exception, been benign, with only few local recurrences treated successfully with operation. This is in contrast to the behaviour of perineural invasion of cutaneous SCCs.…”
Section: Introductionmentioning
confidence: 77%
“…Another strong argument for the benign nature of KAs stems from the clinical fate of patients with KAs demonstrating neural or venous invasion. Neural invasion of KA, as well as a few cases of vascular invasion, have been described in a number of papers . The biological behaviour in all studies and all reported cases have, without exception, been benign, with only few local recurrences treated successfully with operation.…”
Section: Introductionmentioning
confidence: 94%
“…In addition to the recurrence of KA after surgical resection, the trauma of the operation itself is also the cause of KA[ 21 ]. For recurrent KA, combined treatment measures are thus necessary, including surgical resection combined with radiotherapy and injection of triamcinolone acetonide, YAG laser combined with local injection of 5-fluorouracil, and local application of imiquimod after surgical treatment, which can achieve good results[ 18 , 22 , 23 ]. In this case, surgical resection and topical application of tretinoin cream were used for recurrent KA, which effectively prevented disease recurrence.…”
Section: Discussionmentioning
confidence: 99%